Reducing losses in solid-core photonic crystal fibers using chlorine dehydration - Frosz, Michael H.; Ahmed, Goran; Lapshina, Nadezda; Keding, Ralf; Babic, Fehim; Joly, Nicolas; Russell, Philip St. John (Optical Materials Express, 2016)
The fabrication of photonic crystal fibers (PCFs) involves the stacking of multiple preform elements, providing many opportunities for contamination by water vapor or dust particles and causing increased fiber loss. Even after manufacture, diffusion of water vapor into the hollow channels is known to cause a slow increase in loss if the fibers are stored in a humid environment. In this paper we report a systematic study of three methods to reduce OH-related loss in solid-core PCFs: (1) treating the stack (primary preform) with chlorine or oxygen; (2) treating the cane (intermediate preform) with chlorine or oxygen; and (3) using a dry gas for pressurization of the hollow channels during the final step of fiber drawing. Each treatment is independently found effective in reducing OH-related loss, although stack treatment alone is not sufficient if the canes are subsequently stored for a longer time. On the other hand, chlorine-treatment of the canes and/ or using a suitably dry gas using fiber drawing significantly lowers the loss even when the canes have been stored for more than two years in a closed tube at room temperature and at relative humidities in the range similar to 20% to similar to 50%. (C) 2016 Optical Society of America